2021
DOI: 10.3389/fneur.2021.708800
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Injury to the Developing Brain: Emerging Relationship to Early Life Stress

Abstract: Despite the high incidence of brain injuries in children, we have yet to fully understand the unique vulnerability of a young brain to an injury and key determinants of long-term recovery. Here we consider how early life stress may influence recovery after an early age brain injury. Studies of early life stress alone reveal persistent structural and functional impairments at adulthood. We consider the interacting pathologies imposed by early life stress and subsequent brain injuries during early brain developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 237 publications
(143 reference statements)
1
10
0
Order By: Relevance
“…The most common mechanism of injury in our patients was RTAs – one study found domestic accidents to be commonest, 9 but the majority of published literature confirm RTA as the predominant mechanism of injury. 36,10 Likewise, ‘fall from height’ was another significant mechanism of injury, in keeping with most other studies from India; 4,6,7,11 three of the nine traumas under 1 year of age were falls.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The most common mechanism of injury in our patients was RTAs – one study found domestic accidents to be commonest, 9 but the majority of published literature confirm RTA as the predominant mechanism of injury. 36,10 Likewise, ‘fall from height’ was another significant mechanism of injury, in keeping with most other studies from India; 4,6,7,11 three of the nine traumas under 1 year of age were falls.…”
Section: Discussionsupporting
confidence: 83%
“…Due to lack of knowledge, parents are carrying children in two or three wheelers without adequate protection, resulting in a high incidence of falls; injury to a child's developing brain can have both short term and long term damage and the head was the second most commonly injured body area in this study. 11,12 Blunt abdominal injury was the most common type of injury and liver was the most affected organ. Data from developed nations like the USA have shown a high incidence of RTA death in children who are not restrained in their cars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the focus on physical deficits in the early stages of severe brain injury, it is cognitive and behavioral deficits that lead to the significant morbidity that most hinder the ability to resume work and maintain social activities, causing long-term disability and lowering the quality of life [4,10].…”
Section: Discussionmentioning
confidence: 99%
“…It is a neurosurgical disease with high fatality and disabilityrates, which can cause physical, cognitive, emotional, and behavioural symptoms [4] [5] . TBI is second only to cancer and cardiovascular disease in morbidity and mortality and is the leading cause of traumatic death [6] [7] . TBI, which affects an estimated 69 million people worldwide, is usually caused by traffic accidents, falling from high altitudes, extreme sports, and other violent hits to the head that cause short-term memory loss and motor and cognitive dysfunction [8] [9] [10] .…”
Section: Introductionmentioning
confidence: 99%